Tracing the molecular evolution of Foxp2 proteins in vertebrates from fish to tetrapods: Insights into poly-Q tract variation, structural changes, and interaction networks - Koseoglu, Ahmet Efe; Koseoglu, Gulsum Deniz; Ozgultekin, Buminhan; Goc, Bilge Irem; Neziri, Sabina; Ozgenturk, Nehir Ozdemir (ELSEVIER SCI LTD, 2026)
Foxp2 is a transcription factor containing poly-Q repeats, commonly found in brain proteins. It plays essential roles in speech, motor function, cognition, and emotion, and is expressed during embryonic development in the brain, lungs, heart, and intestines. Foxp2 is highly conserved among vertebrates. This study investigated the molecular evolution of Foxp2 by analyzing its sequence, structure, post-translational modifications (N-glycosylation and phosphorylation), positive selection signals, conserved motifs, domains, and interaction networks across five representative vertebrates: human, cattle, coelacanth, zebrafish, and pufferfish. Structural comparison showed closer similarity among human, cattle, and coelacanth, with a poly-Q tract absent in zebrafish and pufferfish. A unique 25-amino acid insertion was identified only in cattle. Two conserved domains were found in all species, while one domain was restricted to human, cattle, and coelacanth. Of 37 predicted motifs, motifs 30-37 associated with poly-Q repeats were exclusive to human, cattle, and coelacanth. Poly-Q tracts are notable due to their links with neurodegenerative disorders such as prion diseases and Huntington's disease. Two distinct N-glycosylation profiles emerged: one shared by human, cattle, and coelacanth, and another by zebrafish and pufferfish. Protein interaction analysis consistently identified Ctb1, Nfatc2, and Tbr1 as partners. Phylogenetic analysis placed coelacanth closer to the human/cattle clade than to teleosts, reflecting its transitional evolutionary status. Together, these integrative bioinformatics results provide new insights into the molecular evolution of Foxp2, highlighting the evolutionary position of coelacanth and the functional relevance of poly-Q repeats in vertebrates.
Keywords: Vertebrate Foxp2 protein; Structural phylogenetics; Poly-Q and PTM conservation; Lineage-specific insertion; Coelacanth; GENE; SPEECH; DISEASES; Life Sciences & Biomedicine - Other Topics; Computer Science